Study on the reuse of high-silica by-product from Lionas Metals Plant to partially replace cement in concrete production - Dang-Nguyen Nguyen (Vietnam Journal of Science, Technology and Engineering, 2025)
This study investigates the reuse of high-silica by-product (HSB) from the Lionas Metals Plant as a partial replacement for cement in concrete production. Four mixtures with 0, 10, 20, and 30% cement replacement by HSB were designed using the absolute volume method at a fixed water-to-binder ratio of 0.45. The study evaluated the effects of HSB on concrete properties, including fresh and dry unit weights (UW), water absorption (WA), compressive strength (CS), ultrasonic pulse velocity (UPV), thermal conductivity (TC), and rapid chloride ion penetration (RCPT). Results showed that increasing the HSB content led to a reduction in both fresh and dry UWs. WA decreased with longer curing times and higher HSB content, while resistance to chloride ion penetration improved significantly. The HSB content resulted in higher CS and UPV while reducing WA, TC, and RCPT. Higher HSB content resulted in greater CS and durability, with the 30% HSB mixture demonstrating outstanding 28-day performance: a maximum CS of 65.04 MPa, the highest UPV of 4902 m/s, the lowest WA of 1.14%, a reduced TC of 1.96 W/(m×K), and an extremely low RCPT value of 179 Coulombs. Microstructural analysis supported these observations. The findings demonstrate HSB’s effectiveness in improving concrete performance and confirm its viability for sustainable concrete production.